The Role of 3D Modeling in Additive Manufacturing: Advances and Applications - Yogesh Kumar Mishra; Ajay Kumar (International Journal of Machine Systems and Manufacturing Technology, 2025)
By making it possible to create intricate, highly functional, and customized components for a range of industries, the combination of 3D modeling and additive manufacturing (AM) has completely changed contemporary production processes. With an emphasis on both the technological advancements in digital design and its real-world applications, this paper examines the critical role that 3D modeling plays in the success of additive manufacturing. 3D modeling, the cornerstone of additive manufacturing, offers the exact geometrical instructions needed to construct objects layer by layer with the least amount of material waste and to create parts that were previously impractical or unaffordable to manufacture using conventional methods. The paper begins by outlining the principles of 3D modeling and their application to AM, noting how advances in digital design have expanded the capability of manufacturing. It discusses major software packages, including CAD systems, slicing programs, and simulation software, to reveal how they make it possible to develop, prepare, and test models prior to printing. Also, an elaboration on how 3D modeling can enhance material efficiency, minimize lead times, and accelerate prototyping is given. Real-world case studies are employed to analyze the day-to-day applications of 3D modeling across industries like consumer goods, healthcare, automotive, and aerospace. Boeing's employment of 3D-printed lightweight parts, patient-specific implant and prosthetic production in healthcare, and automobile prototyping are some examples of how 3D modeling and additive manufacturing are changing product design, customization, and production lifecycles. The research also examines state-of-the-art technologies such as multi-material printing and metal additive manufacturing, illustrating how these innovations depend on sophisticated 3D modeling methods to design elements with novel properties and enhanced functionality.
Keywords: 3D modeling; Additive manufacturing; Digital design; aerospace; and healthcare; automotive